Effects of moisture content to flexural properties of kenaf bast fibre reinforced unsaturated polyester composites - Mohamed Yusoff, Mohd Zuhri; Ishak, Mohamad Ridzwan; Leman, Zulkiflle; Salit, Mohd Sapuan; Abdul Manaf, Mohd Edeerozey (2009)
The usefulness of natural fibres as reinforcement in material composites had been proved for various applications. However, main problem arise is the poor interfacial adhesion bonding between fibre and matrix due to the presence of moisture. However, there were limited numbers of studies that have been carried out to investigate the effects of moisture content to the mechanical properties of kenaf bast fibre composite. Thus, this study is aim to investigate the effect of moisture content to the flexural properties of kenaf bast fibre reinforced unsaturated polyester composites. The fibre was dried in an oven at 80ºC for the duration of 2 hours while another fibre was left as-received at room temperature. Composites of 20% dried and undried kenaf bast fibre reinforced unsaturated polyester were prepared. The flexural properties of specimens subjected to undried fibre were evaluated and compared alongside dried fibre as composites reinforcement by a series of flexural test in accordance to the ASTM D790.